A missing person as a copyright holder - Lewandowska, Ewa (Problems of legality, 2021)
The disappearance of people is a phenomenon that requires in-depth multi-faceted analysis. The law does not regulate the situation of a missing person between their disappearance and being declared dead. During this time, in the understanding of the law, a missing person remains an entity that can dispose of their property rights and personal rights, but because of the disappearance people are unable to do that, so his/her rights are exposed to be lost or unlawfully used by other persons. As a result, many doubts must be faced by people close to the missing person. This work discusses the copyrights of the missing person, its execution and protection in the time between the disappearance and declaring the person dead. As an introduction, the subject of copyright (work) is discussed and the division of copyright into moral rights and property rights is indicated. Next, the paper presents the possible ways of proceeding in the event of a disappearance, including a minor, spouse, and co-creator. The possibility of appointing a custodian and submitting a request to a prosecutor is indicated, and an analogous application of provisions in the event of death is proposed. Moreover, a situation where an action to protect moral/economic copyrights has been brought before a person missing (the proceedings are pending) is noted. Finally, the consequences of declaring a missing person to be dead are discussed. Based on the considerations carried out, it can be concluded that there is no single appropriate legal solution in a situation where there is a need to exercise and protect the personal/economic copyrights of a missing person. The proposed solutions of proceeding in the missing person case are not specifically designed in the event of a disappearance, and their application is not established in practice. It seems that the court should recognize the need to protect the interests of the missing person and allow the proceedings to be conducted when referring to one of the proposed solutions. Adaptation of the indicated solutions, in the face of the forced inactivity of the missing person, should guarantee the protection of his/her rights. De lege ferenda, it is worth considering the general regulation of a person’s situation from the moment of his/her disappearance until he/she is declared dead. This could be done by introducing a provision providing for the possibility of appointing a custodian to handle the missing person’s affairs.